Understanding online communication through Arab eyes - Lindley, Siân; Rode, Jennifer A.; Alsheikh, Tamara (CHI 2010 workshop on Models, Theories and Methods of Studying Online Behavior, 2010)
As we strive towards a unified theory of online communication, we need to understand the role of cultural values in technology adoption and design. Here, in the spirit of defamiliarization, we present key findings of a study of Arab couples using new technologies to maintain long-distance relationships. We demonstrate how Western values are designed into the technology, and how Arabic values play a role in how the technology is used and re-appropriated. In doing so we argue that a unified theory of online communication must use care to ensure mainstream cultural values are not theoretically reified.